Aplikasi Mobile Untuk Mengenal Ragam Profesi Untuk Anak Usia Dini (Studi Kasus: PAUD Terpadu Bakti Nusa, Bengkulu) - Marissa Utami; Dedy Abdullah; Maryatun Nikmah; Marissa Utami (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2021)
The development of mobile-based learning applications is very diverse, ranging from applications for basic education to higher education. Apart from the many types of mobile-based learning applications offered, there is a need for innovation in terms of pedagogical considerations. Based on this, this study tries to develop innovation by making an application to introduce various occupational professions in early childhood. This application will apply the Linear Congruent Method (LCM) algorithm which is used to randomize guessing the images that will be played in the educational game on the introduction of various occupations. As a result of the research, the application was built using the Java and Kotlin programming languages to identify various occupations using the LCM algorithm. This application has features including a main page, a learning page, a quiz page and an about page.